Synthesis and Crystal Structures of 1,1′-Methylene-bis(imidazolidine-2,4-dione) and Alkali Metal Salts - Robert Salchner; Volker Kahlenberg; Roman Lackner; Klaus Wurst; Doris Braun; Gerhard Laus; Herwig Schottenberger (Crystals, 2014)
Single-crystal structures of 1,1′-methylenebis(imidazolidine-2,4-dione) and its sodium and dipotassium salts were determined. Powder X-ray diffraction was also employed to characterize the bulk materials and those phases which did not yield single-crystals. These compounds are of interest for intumescent coatings.